PEMODELAN MESIN DIESEL DUAL FUEL (DDF) MENGGUNAKAN BAHAN BAKAR BIODIESEL DAN GAS HIDROGEN - Winangun, Kuntang; Lostari, Aini; Riani, Novi Indah (TURBO [Tulisan Riset Berbasis Online], 2024)
Vehicle exhaust emissions are the second largest cause of pollution after industry. Therefore, the government is targeting net zero emissions by 2060. One way to reduce fuel consumption is to use biodiesel. However, the use of biodiesel still has many negative impacts on vehicle performance, namely decreased engine performance. One way to reduce exhaust emissions without reducing engine performance is by adding hydrogen gas. This study was conducted with a simulation to determine the phenomena that occur in the combustion chamber of a single-cylinder diesel engine including hot cylinder pressure, the impact of combustion on exhaust emissions. The stages in this study consist of pre-processing, processing and post-processing. The results of this study indicate that the addition of hydrogen gas can increase the heat in the combustion chamber, the impact of increased heat is an increase in cylinder pressure, combustion chamber temperature, NO emissions, and CO emissions. While HC and soot emissions decreased with the addition of hydrogen gas to biodiesel fuel.